Comparison of Heat Transfer and Pressure loss between Circular Tube Heat Exchanger Installed the Delta-Winglet Tapes and Perforated Delta-Winglet Tapes - Ketchat, Niwat; Amattirat, Nopparat; Krittacom, Bundit (Srinakharinwirot University Engineering Journal, 2023)
The heat transfers and pressure loss between the circular tube heat exchanger installed Delta-Winglet Tape (DWT) and the Perforated Delta-Winglet Tape (P-DWT) were compared. The winglet inclination angle (a) was kept at 45o. Two winglet blockage ratios (BR) of 0.20 and 0.30 were examined. Three relative winglet pitches (PR: 1, 2, and 3) were conducted. The experiment was conducted in the tube heat exchanger having a uniform heat flux wall. Air was used as the working fluid flowing through the tube for a Reynolds number of about 4,300 – 24,000. The heat transfer and pressure loss were presented in terms of Nusselt number (Nu) and friction factor (f), respectively. From the experiment, it was found that the Nu and f were increased as increasing BR and decreasing PR. For comparison of the DWT and P-DW, the DWT wing gave a higher Nu value than the P-DWT due to the effect of bores on the P-DWT. Although the intensity of the fluid flow passing the P-DWT was slightly reduced, a decreased heat transfer was obtained. In contrast, the f value of the P-DWT can be reduced better than the DWT resulting in the thermal enhancement factor (TEF) of the P-DWTs gave higher than the DWT. The TEF of the P-DWT was in the range of 0.69-1.12 and the maximum TEF regarded as the optimum point was achieved at BR = 0.30 and PR = 0.10.